Europeanisation and De-Europeanisation Dynamics in Turkey: The Case of Environmental Organisations. Issue 1 (2nd January 2016) - Boşnak, Büke
Abstract: While Europeanisation of civil society in Turkey has received considerable attention, there has been much less interest in how environmental organisations, as key civil society actors, have been affected by Europeanisation/de-Europeanisation dynamics. Interviews with civil society representatives and European Union (EU) and Turkish policy-makers indicate that the EU impact on environmental organisations has been ambivalent, and that Europeanisation dynamics are intertwined with the adverse consequences of these processes. While Turkey's EU candidacy has empowered civil society through both EU-isation and Europeanisation, there has also been a remarkable rise of scepticism towards the EU's civil society strategy and the EU has lost its attractiveness as a normative context in environmental debates.